Effets de cinq prétraitements sur la germination du vène (Pterocarpus erinaceus Poir., Fabaceae) dans la Réserve du Haut Bandama (Côte d’Ivoire) - Bamba, N’golo; Ouattara, Noufou Doudjo; Konan, Djézou; Bakayoko, Adama; Tra Bi, Fezan Honora (European Scientific Journal, ESJ, 2018)
Pterocarpus erinaceus Poir (Fabaceae) is a sudanese multipurpose species ranging in Côte d’Ivoire, at the north of the 8 th parallel. This species is object of illegal exploitation and the survival of its natural populations is strongly threatened. The sustainable management of this resource requires an improvement of its germinative capacities. To achieve this goal, five pretreatments were applied to seeds collected from a population of Pterocarpus erinaceus in the “Réserve du Haut Bandama”. These treatments include flowing water soaking during three days or 72 hours (STE 3), water soaking at 60 ° C (STE 60), and at 100° C (STE 100), removal of the shell of the fruit (SD) and light fire burning (SF) as well as a control (no pretreatment applied, SND). Germination rate (TG), germination time (DG) and mean germination time (GMT) were evaluated. The results showed that the husked seeds have good germination ability with a rate of 68.5% and a germination time of a week. It also appears that the seeds of the species are very sensitive to heat. Indeed no germination was observed under the pretreatments of light fire burning and soaking in boiling water (100 °C). In addition to this, the shell of the fruit is a factor of dormancy (seed coat / pericarp dormancy). This dormancy can be removed with soaking inflowing water.